Air-to-water heat pump assessment: Part 1 – Experimental setup - Doseva Nadezhda (EDP Sciences, 2021)
This paper is part 1 of the investigation on the exergetic and exergoeconomic parameters of an existing system with an air-to-water heat pump unit as a heat source. Part 1 presents the used experimental setup. The main aim of the conducted experimental tests is to develop a model of produced heat transfer rate and energetic COP at different ambient conditions. The obtained data is used in Part 2 of the study where the exergetic and exergoeconomic assessment is carried out. The performance of the considered system is evaluated using Seasonal Exergy Efficiency. Moreover, Part 2 of the study has presented the formulation of the cost of the product, and cost allocation within the heat pump unit based on exergy.